Eksistensi Kaligrafi dalam Peningkatan Maharah Al-Kitabah - Sitorus, Nurul Hafizhah Salsabila; Herba, Nanda Tsabita; Pasaribu, Annisa Khairida; Nst, Hikmatul Fadhilah; Nasution, Sahkholid (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Maharah al-kitabah (writing skills) is the application of complex language skills and abilities. Arabic calligraphy is the art of beautiful writing, whose learning contains how to write letters, words, and sentences in Arabic properly, correctly, and beautifully, so that the writing can be read easily without any errors in writing meaning. The purpose of this research is to analyze the existence of calligraphy in improving maharah al-kitabah. This research is qualitative with a library research approach. Researchers used descriptive analysis method in analyzing research data. Researchers collect data by looking for references to previous journals regarding calligraphy in improving maharah kitabah as a primary data source, and directly analyzing the references used as data sources and drawing conclusions in them. The results showed that calligraphy learning is closely related to kitabah learning. Writing skills or kitabah in Arabic not only require proficiency in expressing the main idea, but also must be proficient in writing letters, words, and sentences in Arabic. Therefore, the existence of calligraphy is important in learning of writing.Â